Foreign Direct Investment In The Banking Sector In New EU Member States: Social Responsibility Of Banks - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper discusses the performance and strategies of banks with foreign participation in the new EU Member States and their attitudes towards socalled ‘socially responsible finance’. The banking sector in the analyzed countries (Czech Republic, Poland and Slovakia) is dominated by foreign capital. The global financial crisis caused a decrease in new annual FDI inflows into the financial intermediation and banking sector of these countries. Some disinvestment occurred in Slovakia and Poland. The foreign-owned banks already operating in the analyzed countries undertook some organizational and financial adjustments to the global economic crisis that allowed them to secure their own position in recipient countries. They are involved in socially responsible activities in the field of culture, sport, environmental protection etc. As trust-based financial institutions. they also showed a kind of responsibility in the field of finance when the crisis occurred.